Managing Pet-Friendly Tourism Experience through The Service-Dominant Logic Perspective: Case Study of Service Design in Thai Hotels - Chatawanich, Somphob; Chatawanich , Maneewan; Srithongna, Krissana (Dusit Thani College Journal, 2025)
The growing trend of pet ownership reflected broader social dynamics and evolving human behaviors that elevated pets to the status of family members. This shift contributed to the emergence of a new tourism segment known as “pet-friendly tourism.” This article aimed to analyze how pet-friendly tourism experiences were co-created through the lens of Service-Dominant Logic (S-D Logic), which emphasized collaborative value creation between service providers and consumers. A conceptual framework and case study methodology were used to examine service design strategies adopted by three leading pet-friendly hotels in Thailand: The Standard Hua Hin, The Peri Hotel, and Kimpton Maa-Lai Bangkok. The study found that pet parents expected empathy-driven service, inclusive spaces, and emotional bonding. Technology played a significant role in shaping personalized experiences and enabling value co-creation. The study contributed to the understanding of niche tourism management and proposed ethical and strategic implications for businesses seeking innovation through emotional engagement and co-experience.